CD117+ cells/telocytes in chronic steatohepatitis and hepatitis C virus infection: histotopographic and quantitative features. - Gavrilyuk, E. M. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. The course of the most common chronic liver diseases depends on the balance in fibrosis and reparative regeneration. Interrelations between these processes depend on many factors, including recently described cellular type CD117+ cells/telocytes which are involved in paracrine regulation. Objective. The aim is to study histotopographic and quantitative features of CD117+ cells/telocytes in chronic steatohepatitis and hepatitis C virus infection. Methods. 20 autopsies with diagnosed alcoholic steatohepatitis, nonalcoholic steatohepatitis and viral hepatitis C (fibrosis stage 2-3, METAVIR) were enrolled in this study. The CD117+ cells/telocytes were evaluated in the liver tissue. Marker quantification was performed by assessing the ratio of stained tissue to the total area of the liver section using image analysis. Differences between groups were analyzed using Student’s t-test; p < 0,05 was considered as significant. Results. Microscopic examination shows presence of CD117+ cells/telocytes in the interstitial compartment, mostly at the margin between the parenchyma and fibrous tissue – an area associated with “stem cell niche”. Such localization confirms the idea about regulatory role of CD117+ cells/telocytes in liver fibrosis and regeneration, which depends on direct intercellular contacts and paracrine effects. Evaluation of CD117+ cells/telocytes area in the liver section shows the higher degree in chronic steatohepatitis group (1,98±0,25) than in patients with hepatitis С virus infection (1,15±0,4) (p > 0,05). Conclusion. Differences in the amount of CD117+ cells/telocytes in the area of “stem cell niche” in patients with chronic steatohepatitis and hepatitis C virus infection correlates with the hypothesis about existence of multiple pathogenetic pathways of fibrosis and regeneration which depends on the etiologic factors or secondary influences induced during the course of the disease.